Towards evidence-based emergency medicine: best BETs from the Manchester Royal Infirmary. BET 2: early nasogastric feeding indicated for severe acute pancreatitis - Correia, I (2016)
A short-cut review was carried out to establish whether early enteral feeding is indicated in acute pancreatitis. A total of 33 papers was found using the reported search, of which four represented the best evidence to answer the clinical question. The author, date and country of publication, patient group studied, study type, relevant outcomes, results and study weaknesses of these best papers are tabulated. The clinical bottom line is that patients with acute severe pancreatitis should receive enteral feeding.